Religious attitude scale in students of human medicine - Rivera-Encinas, María Teresa (2019)
Objective: To establish the validity and reliability of the Religious Attitude Scale (RAS) in a sample of medical students from a Peruvian private university. Materials and methods: An observational and cross-sectional study was conducted. The RAS was administered to a sample of 687 medical students to assess the psychometric properties. Results: The mean score of the RAS was 62.97 ± 15.74. Differences in gender (p = 0.011), academic year (p = 0.035) and religion (p = 0.000) stand out. Three factors with eigenvalues of 9.34, 1.53 and 1.02 were found, each contributing 35.22 %, 17.68 % and 17.09 % of the total variance explained in t he rotation, which accounts for 70 % of the total variance. The RAS has an acceptable internal consistency (Cronbach's alpha = 0.94); however, in its 14-item version it increases to 0.951. Conclusions: It can be concluded that the RAS, in its 14-item version, has adequate psychometric properties to evaluate the attitude of the population of Peruvian students of human medicine toward religion.